Comparative Analysis of Media Coverage of the Turkish Drone (Akinci) in the Iranian President's Helicopter Search - Sakhidad Mahdiyar; Sabghatullah Ghorzang (Journal of Communication Research, 2026)
This study investigates how international news media framed the role of Bayraktar Akıncı drone in the search operation following the May 2024 helicopter crash that resulted in the death of the president of Iran. Drawing on Entman’s framing theory, the study aims to identify dominant frames and examine how the evaluative tone toward Turkish and Iranian technological capabilities varies across media. Using qualitative content analysis, seven English-language articles from Anadolu Agency, IRNA, Frontline-The-Hindu, Reuters, The Independent UK, Newsweek, and CBS News were coded in MAXQDA. Applying Entman’s four framing functions, the analysis shows that operational–technological framing defined the crash primarily as a logistical and environmental problem solvable through UAV capability (problem definition and treatment recommendation). In contrast, Iranian and select Western outlets reoriented causal attribution by questioning the drone’s effectiveness (causal interpretation) and embedded nationalist or geopolitical evaluations when assessing technological performance (moral evaluation). Variations in tone functioned as indirect geopolitical signaling, transforming crisis reporting into a form of symbolic “drone diplomacy,” where technological performance operated as a proxy for national prestige and strategic positioning. Tonal patterns were closely aligned with geopolitical proximity: Turkish and neutral outlets were largely positive or balanced, whereas Iranian and some Western outlets were largely skeptical or critical. Source usage played a pivotal role in shaping frames, with Turkish and Iranian outlets relying heavily on domestic official statements, reinforcing national narratives.